Relationship between IoT Service User Quality and Network QoS Factors - Khamosh, Abdurauf; Ahmadi, Abdul Rahim; Anwer, Mohammad; Hamdard, Javid; Aminzai, Sadiq; Nasrat, Nasratullah (Journal for Research in Applied Sciences and Biotechnology, 2023)
The Internet of Things (IoT) is a complete network of networked computer devices, digital and mechanical equipment, and the capacity to send data over the Internet based on machine to machine interaction. It is also known as the Internet of Everything (IoE). The Internet is a packet-switched network, which means that the Quality of Service (QoS) elements (such as packet loss, latency, jitter, and so on) have an influence on the Quality of Experience (QoE) for the Internet of Things services. This research used a subjective evaluation method in order to evaluate the relationship between the quality of service (QoS) measures such as packet loss, latency, and jitter and the quality of experience (QoE) for Internet of Things services. In addition to that, a mapping model from quality of service to quality of experience was suggested. According to the results of this research, there is a close connection between the subjective opinion score and the quality of service (QoS) variables such as packet loss, latency, and jitter. The results of this investigation open up possibilities for additional research into the quality of experience of Internet of Things services.